2010
DOI: 10.1681/asn.2009101065
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Donor-Specific HLA Antibodies Predict Outcome in Kidney Transplantation

Abstract: The clinical importance of preexisting HLA antibodies at the time of transplantation, identified by contemporary techniques, is not well understood. We conducted an observational study analyzing the association between preexisting donor-specific HLA antibodies (HLA-DSA) and incidence of acute antibody-mediated rejection (AMR) and survival of patients and grafts among 402 consecutive deceaseddonor kidney transplant recipients. We detected HLA-DSA using Luminex single-antigen assays on the peak reactive and curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
583
8
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 715 publications
(647 citation statements)
references
References 44 publications
31
583
8
25
Order By: Relevance
“…23 Beads showing a normalized MFI.500 were considered positive. For each patient, we recorded the number, class, specificity, and MFI of all DSAs.…”
Section: Dsasmentioning
confidence: 99%
“…23 Beads showing a normalized MFI.500 were considered positive. For each patient, we recorded the number, class, specificity, and MFI of all DSAs.…”
Section: Dsasmentioning
confidence: 99%
“…12,13 Moreover, Burns et al 14 found that in acute ABMR with positive pretransplant B-cell FCXM, complement activation within the allograft, as indicated by C4d deposition in peritubular capillaries, was related to DSA levels. These data confirm that the main pathophysiological mechanism of acute ABMR occurring early after transplant is related to the presence of high levels of DSAs, which result in the local activation of the classic complement pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from numerous investigators reported of AMR and/or graft loss in patients who's donor-specific antibody (DSA) were undetectable by complement dependent cytotoxicity assays but present by multiplex solid phase assays (36)(37)(38)(39)(40). Thus, the preferred donor lacks the HLA antigen(s) corresponding to antibodies identified by solid phase technology.…”
Section: Theory Versus Realitymentioning
confidence: 99%
“…There are at least three approaches: (i) Statistical; establishing a fluorescence level (cutoff) significantly above background; (ii) Practical; correlating with a crossmatch result and (iii) Clinical; identifying a level that predicts immediate/early graft loss. Previous studies have reported correlations between MFI levels of donor-specific HLA antibodies and either clinical outcome (40,47) or crossmatch results (54), leading to the reasonable expectation that a threshold level of fluorescence can be established above which an antibody can be considered as present and below which, absent. Unfortunately, it is not that simple and straightforward.…”
Section: Complicationsmentioning
confidence: 99%